Selective Reduction of Amino Allenephosphonates: Preparation of α‐Amino Vinylphosphonates. Issue 33 (9th October 2013) - Adler, Pauline; Gomes, Filipe; Fadel, Antoine; Rabasso, Nicolas
Abstract: α‐Amino vinylphosphonates were prepared by chemo‐ and stereoselective reduction of α‐amino allenephosphonates. Our results showed that the substituents on the allene, phosphonate, and nitrogen moieties affected the stereoselectivity of the reduction. Z ‐α‐Amino vinylphosphonates were prepared with good selectivities up to > 95:5. Abstract : An efficient synthesis of α‐amino vinylphosphonates by simple hydrogenation of α‐amino allenephosphonates with a poisoned palladium catalyst is described.